Yakut Language in Modern Education System of Republic of Sakha (Yakutia): Actors, Debates, New Challenges - A. N. Bitkeeva; N. I. Ivanova; M. Ya. Kaplunova (Научный диалог, 2022)
The issues of the Yakut language functioning — the native language of the majority of the Arctic zone of the Republic of Sakha (Yakutia) inhabitants — in the field of education are considered. The authors proceed from the fact that, being one of the key areas (along with such regulated areas of communication as the sphere of official office work, the media, science, etc.) necessary for the preservation and sustainable development of the language, the education sector is able to reflect the current language situation in the region, identify risks and threats to the existence of a particular language. The relevance of the study is due to the fact that we are on the eve of the International Decade of Indigenous Languages (2022—2032), proclaimed by the UN General Assembly. The results of a comparative analysis of the status of the Yakut language de jure and de facto based on the analysis of relevant legislative acts and the results of surveys among residents of Yakutia in 2021 are presented. It is concluded that the analysis carried out makes it possible to judge the negative dynamics, which manifests itself in a moderate but continuous decrease in linguistic competence among native speakers of the languages of the peoples of the Russian Federation. It is noted that this situation at the present stage is noticeable only to experts and philologists, but it poses a certain threat to the existence of the language in the long term.